Disability studies : a student's guide - Cameron, Colin, 1964- ([Los Angeles] : SAGE, 2016)
Bringing together a range of expert voices to tackle the essential topics relevant to the study of disability from a social perspective, this interdisciplinary introduction includes over 50 chapters relevant across health and social care.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 20, 2016).
Keywords: Disability studies -- Great Britain; People with disabilities -- Great Britain; Sociology of disability -- Great Britain